2019
DOI: 10.1142/s0129054119400227
|View full text |Cite
|
Sign up to set email alerts
|

On Average Behaviour of Regular Expressions in Strong Star Normal Form

Abstract: For regular expressions in (strong) star normal form a large set of efficient algorithms is known, from conversions into finite automata to characterisations of unambiguity. In this paper we study the average complexity of this class of expressions using analytic combinatorics. As it is not always feasible to obtain explicit expressions for the generating functions involved, here we show how to get the required information for the asymptotic estimates with an indirect use of the existence of Puiseux expansions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…Second, the results of Koechlin et al do not imply that asymptotic estimates obtained by considering the whole set of regular expressions are different from those obtained by using a more refined set with less equivalent expressions. For instance, some results obtained for expressions in strong star normal form coincide with the ones for standard regular expressions [2]. In order to further sustain the above claim, in this paper we consider the set R of regular expressions avoiding an absorbing pattern which extends the pattern in the example above and was the one considered by Koechlin et al It is shown that, although the set R is significantly smaller than the set RE, the asymptotic estimates for the size of the Glushkov automaton on these sets is the same.…”
Section: Introductionsupporting
confidence: 64%
“…Second, the results of Koechlin et al do not imply that asymptotic estimates obtained by considering the whole set of regular expressions are different from those obtained by using a more refined set with less equivalent expressions. For instance, some results obtained for expressions in strong star normal form coincide with the ones for standard regular expressions [2]. In order to further sustain the above claim, in this paper we consider the set R of regular expressions avoiding an absorbing pattern which extends the pattern in the example above and was the one considered by Koechlin et al It is shown that, although the set R is significantly smaller than the set RE, the asymptotic estimates for the size of the Glushkov automaton on these sets is the same.…”
Section: Introductionsupporting
confidence: 64%